2017
DOI: 10.1002/dc.23735
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of fine‐needle aspiration cytology of lesions involving bone

Abstract: Our findings indicate that FNA of bone lesions is a useful diagnostic technique with high sensitivity, particularly when the cytologic findings are interpreted in conjunction with the core biopsy and pertinent clinical and radiologic findings. In addition, ROSE followed by open, dynamic communication with the performing radiologist leads to an extremely low rate of inadequate core biopsy specimens, resulting in optimal patient diagnosis and management. Diagn. Cytopathol. 2017;45:608-613. © 2017 Wiley Periodica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…Numerous publications have reported that CT-guided percutaneous core-needle biopsy is a well-established technique and is effective for the initial diagnosis of musculoskeletal lesions, with a measured diagnostic yield ranging between 70 and 89% and a reported accuracy between 61 and 98% [211]. These results confirm the high sensitivity of CT-guided percutaneous needle biopsy for the diagnosis of bone tumors through the use of a minimally invasive procedure, which is associated with cost savings and fewer biopsy complications than open surgical biopsy [6, 7, 1014]. However, the disadvantage of this guided biopsy method is that metabolically active lesions without distinctive morphology may not be reliably assessable by CT-guided biopsy, and the false-negative biopsy rate of such lesions may be substantially higher with CT-guided biopsy [15].…”
Section: Introductionmentioning
confidence: 57%
“…Numerous publications have reported that CT-guided percutaneous core-needle biopsy is a well-established technique and is effective for the initial diagnosis of musculoskeletal lesions, with a measured diagnostic yield ranging between 70 and 89% and a reported accuracy between 61 and 98% [211]. These results confirm the high sensitivity of CT-guided percutaneous needle biopsy for the diagnosis of bone tumors through the use of a minimally invasive procedure, which is associated with cost savings and fewer biopsy complications than open surgical biopsy [6, 7, 1014]. However, the disadvantage of this guided biopsy method is that metabolically active lesions without distinctive morphology may not be reliably assessable by CT-guided biopsy, and the false-negative biopsy rate of such lesions may be substantially higher with CT-guided biopsy [15].…”
Section: Introductionmentioning
confidence: 57%
“…Currently, the frequently used biopsy technologies mainly include ne-needle aspiration, core needle biopsy, incision biopsy, and excision biopsy. Owing to the involvement of small trauma, less complications, lower cost, and ease of operation, the rst two technologies are favored by bone oncologists [25,26] . However, there are several other factors that affect the diagnosis rate with the use of these two approaches.…”
Section: Discussionmentioning
confidence: 99%
“…36 Although it has several advantages, such as the cost, speed, and ease of performing, and it has already shown high sensitivity in the biopsy of several other organs, FNA is not often used for the biopsy of MSK tumors. 45,46 The main reason is the structure and heterogeneity of the mesenchymal tumors that have similarities and can overlap cytomorphologically, and the low quantity of obtained material that is insufficient for various morphological, immunohistochemical, or molecular analyses. 45,46 Several studies showed low accuracy of FNA in the biopsy of MSK tumors compared with core needle biopsy, whereas others claimed a high sensitivity.…”
Section: Factors Associated With Success Of the Imaging-guided Biopsymentioning
confidence: 99%
“…45,46 The main reason is the structure and heterogeneity of the mesenchymal tumors that have similarities and can overlap cytomorphologically, and the low quantity of obtained material that is insufficient for various morphological, immunohistochemical, or molecular analyses. 45,46 Several studies showed low accuracy of FNA in the biopsy of MSK tumors compared with core needle biopsy, whereas others claimed a high sensitivity. 45,46 Therefore FNA is usually reserved for the diagnosis of metastases or recurrent tumors that were previously documented, 47 and some centers do not perform it at all.…”
Section: Factors Associated With Success Of the Imaging-guided Biopsymentioning
confidence: 99%
See 1 more Smart Citation